Phylogenomic study and organellar genomic characterization of gracilarioids seaweeds (Gracilariaceae, Rhodophyta) - Iha, Cíntia (2018)
Gracilariaceae is a worldwide distributed family that includes numerous economically important species. Currently, five genera are recognized in the Gracilariaceae: Gracilariophila (parasitic), Curdiea, Melanthalia, Gracilaria, and Gracilariopsis. Some species of Gracilaria were taxonomically transferred to Hydropuntia. However, this genus is quite controversial. High-throughput sequencing (HTS) techniques has led to an increase in studies using complete organellar genomes, which have been used to infer phylogenetic relationships in Rhodophyta and the investigation of other aspects of red algal genomes, including gene synteny and horizontal gene transfers (HGT). HTS also facilitated the search for extrachromosomal plasmids and its influence in the organellar genomes by HGT. We applied HTS to assemble and annotate organellar genomes (mitochondria and chloroplast) from seven species of Gracilariaceae using Illumina HiSeq 2500 platform. We also received raw reads of 31 samples of Gracilariaceae from Dr. Goia Lyra that were analysed and included in our work. We used these data, combined with published genomes, to infer phylogenies and compare the genome architecture of these species representing the main lineages in Gracilariaceae. The mitochondrial and chloroplast genomes were highly conserved in gene synteny among the species, and variation mainly occurred in regions where insertions of plasmid-derived sequences (PDSs) were found, which were similar to known red algae extrachromosomal plasmids. In mitochondrial genomes, the PDS insertions were in two regions where the transcription direction changes: between cob and trnL genes, and trnA and trnN genes. PDS insertions in chloroplast genome were in different positions, but generally found between psdD and rrs genes. The bacterial leuC/leuD operon was found in Gracilaria tenuistipitata, G. chilensis, M. intermedia chloroplasts genomes, and also in G. vermiculophylla extrachromosomal plasmid. Phylogenetic trees show two different origins of leuC/leuD: genes found in chloroplasts and plasmids were close to proteobacteria, and genes encoded in the nucleus are close to Viridiplantae and cyanobacteria. Gracilariaceae may be a good model to study the impact of PDS in genome evolution due to the frequent presence of these sequences inserted in organellar genomes. Our phylogenetic analyses demonstrated similar evolutionary histories between the chloroplast and mitochondrial genomes. However, chloroplast phylogeny was better resolved with full support. Our taxonomical sampling supports the presence of three main lineages: Melanthalia/Curdiea, Gracilariopsis and Gracilaria. Melanthalia intermedia was sister to a monophyletic clade including Gracilaria and Gracilariopsis, which were resolved as monophyletic genera. Furthermore, the characteristics of organellar genome architecture, Gracilariopsis and Gracilaria genera are also supported by the loss of the plastid gene petP in Gracilaria and the rearrangement position of the gene trnH in the mitochondrial genome. Beside this, we found no support for the genus Hydropuntia as originally proposed